The good salted egg using AHP - Ayshwarya B.; Nguyen P.T.; Alfian F.Y.; Hashim W.; Shankar K.; Aprilda Y.; Ipnuwati S.; Melnikov P.A.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
In the globalization era like nowadays, advertising marketing activities have become a trend in the world of communication to market products to the public. In order to be able to popularize a product that is less known by public, marketing can be an effective means of introducing the product to the wider community. The subjects in this study were decision support systems using the Analitical Hierarchy Process (AHP) method and the results of AHP calculations that can provide opportunities for program manager to be able to build ideas and define existing problems by making assumptions in a hierarchy and then get the desired solution and apply intelligently a complex mathematical approach based on a qualitative approach that can be accepted by all stakeholders and program managers. In this study, it was observed to consist of two factors, namely the factors of constraint and supporting factors with the criteria and sub-criteria considered by the two factors and alternatives that would later be chosen as the best marketing strategy for increasing sales of salted eggs. Based on the results of the study, alternative A1 produced a weight of 17 by occupying priority 1, alternative A2 produced a weight of 10.6 with occupying priority 2. 2019, Blue Eyes Intelligence Engineering and Sciences Publication. All rights reserved.